Religious Diversity and Development in Sarawak : A Linguistic Perspective - Dilah, Tuah (2024)
Abstract: This study explores the intricate relationship between linguistic diversity and religious development in Sarawak, Malaysia, a region renowned for its rich tapestry of ethnic and religious identities. With a population comprising predominantly Bumiputera (75.7%) and Chinese (23.8%), and a variety of religions - Christianity (50.1%), Islam (34.2%), and Buddhism (12.8%)—the research employs qualitative methods to analyse secondary data and field observations. It focuses on how language shapes religious practices and interfaith dialogue. The findings reveal that language significantly influences religious expression and identity formation. Indigenous languages such as Iban and Bidayuh, alongside Malay and English, serve as bridge languages for communication. The study emphasises the role of translations in fostering understanding and illustrates cultural richness through code-switching during religious ceremonies. Ultimately, this research underscores the vital interplay between language and religion in promoting social development and cultural continuity. It suggests that preserving indigenous languages and enhancing interfaith dialogue are essential for maintaining Sarawak's multicultural heritage. Keyword: Religious Diversity; Linguistic Diversity; Sarawak; Interfaith Dialogue; Indigenous Languages